Fast cycle organization development : a fieldbook for organization transformation - Anderson, Merrill C. (South-Western College, 2000)
This book is divided into five parts: Foundations; Change directed at the Organizational Level; Change directed at Teams; Change directed at Individuals; Summary and Synthesis.